Knowledge and attitudes of nurses towards alcohol and related problems: the impact of an educational intervention - Janaina Soares; Divane de Vargas; Maria Lucia Oliveira de Souza Formigoni (SciELO, 2013)
An exploratory study of quasi-experimental approach that aimed to verify the impact of an educational intervention on attitudes and knowledge of nurses towards alcohol use and associated problems. The sample included 185 nurses, divided into two groups: 84 submitted to a training course and formed the experimental group. Data were collected through a knowledge survey and an attitude scale. The attitudes of the participants of both groups were positive. There were no significant differences between groups in relation to knowledge. The strongest predictors of positive attitudes were possessed preparation to act with chemical dependents (OR = 2.18), "have received increased workload during graduation on the theme, 'alcohol and other drugs'" (OR = 1.70), and "completed graduate school" (OR = 2.59). The educational intervention had a positive impact on the attitudes of nurses towards alcoholics, work and interpersonal relationships with such clientele.